Immunogenicity, Safety, and Clinical Eﬀectiveness of the 23-Valent Pneumococcal Polysaccharide Vaccine in Patients With Spondyloarthritis (Preliminary Data) - M. M. Baranova; N. V. Muravyeva; B. S. Belov; M. V. Cherkasova; Zh. G. Verizhnikova; T. V. Korotaeva (Антибиотики и Химиотерапия)
Background. Immunosuppressive drugs are widely used for the treatment of patients with spondyloarthritis (SpA) to eﬀectively control the activity of the disease. At the same time, the use of these drugs is associated with an increased risk of developing infections of the upper and lower respiratory tract, which can be prevented by vaccination. The aim of the study was to evaluate the immunogenicity, safety, and clinical eﬃcacy of the 23-valent pneumococcal  polysaccharide vaccine (PPV-23) in patients with SpA. Material and methods. The study included 54 patients with SpA: 39 with ankylosing spondylitis, and 15 with psoriatic arthritis. Most patients had a history of two or more cases of lower respiratory tract infections, 2 patients reported a monthly exacerbation of chronic sinusitis, one patient reported the development of otitis every 2–3 months. 72% of patients received immunosuppressive therapy at the time of inclusion in the study. PPV-23 was administered in the amount of 1 dose (0.5 ml) against the background of ongoing antirheumatic therapy. The level of antibodies to pneumococcal capsular polysaccharide was determined using the EIA PCP IgG kit (TestLine Clinical Diagnostics s.r.o., Czech Republic) at baseline, after 1, 3, and 12 months after vaccination. The tolerability of PPV-23, the eﬀect of vaccination on SpA activity (according to the dynamics of the BASDAI index), and the incidence of upper and lower respiratory tract infections were assessed. Results. The concentration of antibodies to pneumococcal capsular polysaccharide was signiﬁcantly higher 1, 3, and 12 months after vaccination compared to baseline. There was no negative eﬀect of vaccination on the activity of SpA and the emergence of «new» autoimmune disorders. The vaccine was well tolerated by 76% of patients., Only one patient developed pneumonia during the observation period. Patients suﬀering from frequent sinusitis and otitis reported the absence of these infections after vaccination. Conclusions. Preliminary results of the study indicate suﬃcient immunogenicity, safety, and clinical eﬃcacy of PPV-23 in patients with SpA.